Pengaruh Pelatihan terhadap Peningkatan Produktivitas Kerja Karyawan Rumah Batik Azmiah Kelurahan Olak Kemang Kecamatan Danau Teluk Kota Jambi - M Alpin Syahrir; M Zahari MS; Ubaidillah Ubaidillah (Universitas Batanghari Jambi, 2019)
The Purpose Of This Study Was To Determine The Form Of Employee Training And To Determine The Effect On The Employee Training Of Work Productivity On House Of Batik Azmiah Kelurahan Olak Kemang Kecamatan Danau Teluk Jambi City. Productivity Is The Trigger Of Job Training. Lack Of Productivity Then Required Job Training On Employees. Thus, Low Work Productivity Can Be Overcome By Job Training. House Of Batik Azmiah Has 50 Employees And Is The Biggest Batik Business In Jambi, But Its Marketing Outside Jambi Province Such As Jakarta, Surabaya, Kalimantan And Even Its Marketing Has Reached Foreign Countries Such As India And China. This Research Shows The Positive Influence Between Training On Work Productivity Of Employees Of House Of Batik Azmiah Jambi City Which Is Shown By The Regression Equation Is As Follows: Y = (-1,775) + 1,508 X. Constant Of -1,775 Means If Variable Of Training Of Constant, Hance Work Productivity Employee House Of Batik Azmiah Jambi City Constant. Coefficient Of Training Variables 1,508 Means Training Variables Increased By 1% Then Employee Work Productivity House Of Batik Azmiah Jambi City Will Experience An Increase Of 1,508 With The Assumption Constant. For The Thitung Of 7,037 > Ttabel Of 1.67722. Meaning There Is A Significant Influance Between Training Variable (X) On The Variable (Y) Work Productivity Employee House Of Batik Azmiah Jambi City. The Implementation Of The Training Has A Positive Effect On The Increase Of Work Productivity (Y). This Happens Because The Employee Of House Of Batik Azmiah Jambi City Have A High Spirit In The Effort To Meet The Job Compelation Target After The Training.